2020
DOI: 10.1186/s13287-020-01617-7
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles derived from human Wharton’s jelly mesenchymal stem cells enhance autophagy and ameliorate acute lung injury via delivery of miR-100

Abstract: Objectives: Microvesicles (MVs) derived from human Wharton's jelly mesenchymal stem cells (MSC-MVs) were demonstrated to ameliorate acute lung injury (ALI). We have previously found that MSC-MV-transferred hepatocyte growth factor was partly involved in their therapeutic effects. Since MSC-MVs also contained a substantial quantity of miR-100, which plays an important role in lung cancer and injury, we speculated that miR-100 might similarly account for a part of the therapeutic effects of MSC-MVs.Methods: MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Characteristics of MSC treatments in lung diseases (completed clinical trials) EVs also transferred miR27a-3p / miR146a to modulate macrophage polarization[59,62]. Besides miRNAs, Zhu et al and Tang et al have demonstrated that MSC-EVs (30.9 ± 17.0μg protein/30ul or isolated from 3*10 6 MSCs/30ul) are capable of reducing inflammatory cell influx, protein permeability, MIP2 production, extravascular lung water, and increasing IL-10 secretion in the LPS-induced mouse models[63,64].…”
mentioning
confidence: 99%
“…Characteristics of MSC treatments in lung diseases (completed clinical trials) EVs also transferred miR27a-3p / miR146a to modulate macrophage polarization[59,62]. Besides miRNAs, Zhu et al and Tang et al have demonstrated that MSC-EVs (30.9 ± 17.0μg protein/30ul or isolated from 3*10 6 MSCs/30ul) are capable of reducing inflammatory cell influx, protein permeability, MIP2 production, extravascular lung water, and increasing IL-10 secretion in the LPS-induced mouse models[63,64].…”
mentioning
confidence: 99%
“…Silencing of mTOR or overexpression of autophagy-related proteins in epithelial cells reduced the production of cytokines IL-6 and IL-8[ 109 ]. Chen et al [ 110 ] found that miR-100 present in human WJ-MSCs-derived exosomes (extracellular vesicles, EVs) downregulated mTOR in rat AT-II cells. Treatment with MSCs-derived EVs activated autophagy but inhibited apoptosis and secretion of pro-inflammatory cytokines in bleomycin-treated rat epithelial cells through mTOR downregulation[ 110 ].…”
Section: Mscs Promote Repair Of Tissue Damagementioning
confidence: 99%
“…Chen et al [ 110 ] found that miR-100 present in human WJ-MSCs-derived exosomes (extracellular vesicles, EVs) downregulated mTOR in rat AT-II cells. Treatment with MSCs-derived EVs activated autophagy but inhibited apoptosis and secretion of pro-inflammatory cytokines in bleomycin-treated rat epithelial cells through mTOR downregulation[ 110 ]. The protective and repair functions of the MSCs were found to be mediated by p70S6K1[ 111 ], an isoform of S6K1, which is the downstream target of mTOR[ 65 ].…”
Section: Mscs Promote Repair Of Tissue Damagementioning
confidence: 99%
“…144 A potential drawback is that cellular components internal to cellularly-produced exosomes may also be delivered along with any loaded cargo. 142,150152 Exosomes have been used in mice for delivery to brain 144 and lymph nodes 151 without noticeable toxicity as long as the cell source was syngeneic. Safety studies will be the first major hurdle for exosome delivery to humans since unapproved exosome containing products (from the cells in which the exosomes are produced) have been warned against by the FDA.…”
Section: Future Usesmentioning
confidence: 99%